ZnO nanowire as well as preparation method and application thereof
ZnO nanowires were prepared by microwave-assisted hydrothermal method, which solved the problem of fewer active sites in existing ZnO nanomaterials and improved their catalytic, gas-sensitive and adsorption properties. They are suitable for gas sensing, energy storage and catalysis, and show excellent performance in hydrogen sensors in particular.
Patent Information
- Application Number
- CN202410430045.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-10
- Publication Date
- 2025-10-17
AI Technical Summary
Existing one-dimensional ZnO nanomaterials have regular shapes and few active sites, resulting in limited performance.
ZnO nanowires were prepared by microwave-assisted hydrothermal method. ZnO nanoparticles with a particle size of 5 to 50 nm were interconnected to form a beaded structure. Polyvinyl pyrrolidone was used as a structure-directing agent to control the growth direction of the nanowires. ZnO nanowires with an aspect ratio of 80 to 350 and a specific surface area of 100 to 200 m2/g were prepared.
The catalytic performance, gas-sensing performance and adsorption performance of ZnO nanowires are improved, making them suitable for gas sensing, energy storage and catalysis, especially in hydrogen sensors, where they can quickly and accurately detect hydrogen content.
Smart Images

Figure CN120793997A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of nanomaterials, in particular to a ZnO nanowire and a preparation method and application thereof. BACKGROUND
[0002] ZnO is a common n-type semiconductor material, which has excellent characteristics such as wide direct band gap, high exciton binding energy and stable photoelectric and thermal chemical properties, and is widely used in catalysis, optics, antibiosis and ultraviolet shielding fields.
[0003] In recent years, researchers have prepared ZnO nanoparticles with different morphologies such as zero-dimensional, one-dimensional, two-dimensional and three-dimensional through various methods. The successful preparation of these morphological ZnO nanoparticles further improves the performance of ZnO nanomaterials. One-dimensional ZnO nanomaterials such as ZnO nanowires, nanobands, nanotubes and nanorods are favored by researchers due to their excellent photoelectric and sensing properties. Common methods for preparing one-dimensional ZnO nanomaterials include chemical vapor deposition, template method, electrospinning and hydrothermal synthesis. Most of the nanowires obtained by these methods are one-dimensional ZnO nanomaterials with regular shapes and few active sites, which limits their performance. SUMMARY
[0004] The present application aims to overcome the problem that the current one-dimensional ZnO nanomaterials have regular shapes and few active sites, which limits their performance, and provides a ZnO nanowire and a preparation method and application thereof.
[0005] To achieve the above-mentioned purpose, the present application provides a ZnO nanowire formed by connecting ZnO nanoparticles to each other, wherein the particle size of the ZnO nanoparticles is 5-50 nm.
[0006] Preferably, the length-diameter ratio of the ZnO nanowire is 80-350, and the specific surface area is 100-200 m 2 / g.
[0007] Preferably, the diameter of the ZnO nanowire is 30-150 nm, and the length is 1-10 μm.
[0008] The second aspect of the present application provides a preparation method of a ZnO nanowire, which comprises the following steps:
[0009] (1) mixing urea, water, a zinc source solution and a structure-directing agent to obtain a mixture;
[0010] (2) microwave heating the mixture;
[0011] (3) sintering the product obtained in step (2) at 250-500℃;
[0012] The structure-directing agent is a water-soluble organic substance containing a pyrrolidone group.
[0013] Preferably, in step (1), the structure-directing agent is polyvinylpyrrolidone and / or N-methylpyrrolidone.
[0014] Preferably, step (1) specifically comprises:
[0015] Urea and water are mixed, and then added dropwise into a zinc source solution, followed by mixing with a structure-directing agent to obtain a mixture.
[0016] Preferably, in step (1), the zinc source is selected from one or more of zinc acetate, zinc nitrate and zinc sulfate.
[0017] Preferably, in step (1), the concentration of the zinc source in the zinc source solution is 0.03-0.2 mol / L.
[0018] Preferably, in step (1), the molar ratio of the amounts of the zinc source, urea and structure-directing agent is 1:1.5-5:0.001-0.01.
[0019] Preferably, in step (2), the microwave heating conditions include a microwave power of 900-1500 kW, a reaction temperature of 90-150℃ and a reaction time of 10-50 min.
[0020] Preferably, in step (3), the sintering time is 0.5-4 h.
[0021] The third aspect of the present application provides a ZnO nanowire prepared by the method described above.
[0022] The fourth aspect of the present application provides a use of the ZnO nanowire described above in the fields of gas sensing, energy storage, catalysis or adsorption.
[0023] The fifth aspect of the present application provides a hydrogen sensor, which comprises a gas-sensitive material, and the gas-sensitive material is the ZnO nanowire described above.
[0024] In the technical solution provided by the present application, the ZnO nanowire is formed by ZnO nanoparticles with a particle size of 5-50 nm connected to each other, and has a special string-bead structure. This structure not only maintains the characteristics of high aspect ratio and high specific surface area of the ZnO nanowire, but also exposes more active sites, which is conducive to improving the catalytic performance, adsorption performance and gas-sensitive performance of the ZnO nanowire. Therefore, the hydrogen sensor prepared from the ZnO nanowire can quickly and accurately detect the hydrogen content. BRIEF DESCRIPTION OF DRAWINGS
[0025] Figure 1is a scanning electron microscope image of the basic zinc carbonate obtained in step (2) in Example 1 of the present application;
[0026] Figure 2 is a scanning electron microscope image of the ZnO nanowire prepared in Example 1 of the present application;
[0027] Figure 3 is an XRD pattern of the basic zinc carbonate obtained in step (2) in Example 1 of the present application;
[0028] Figure 4 is an XRD pattern of the ZnO nanowire prepared in Example 1 of the present application;
[0029] Figure 5 is the test result of the hydrogen sensing performance of the ZnO nanowire prepared in Example 1 of the present application at room temperature. DETAILED DESCRIPTION
[0030] The specific embodiments of the present application will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are merely intended to illustrate and explain the present application, and are not intended to limit the present application.
[0031] The endpoints of the ranges and any values disclosed herein are not limited to the precise values stated. The endpoints of the ranges and any values are understood to be approximate values. The exact values are understood to be within the range of values. Any numerical range recited herein is intended to include all sub-ranges subsumed therein. For example, a range of 1 to 10 is intended to include all sub-ranges between and including the values of 1 and 10, e.g., 1 to 6.1, 1 to 4.5, 1 to 2.5, 2 to 6.1, 2 to 4.5, 2 to 10, etc.
[0032] The present application provides a ZnO nanowire formed by ZnO nanoparticles with a particle size of 5-50 nm being connected to each other, wherein the ZnO nanowire has an aspect ratio of 80-350 and a specific surface area of 100-200 m 2 / g.
[0033] In the present application, the particle size of the ZnO nanoparticles refers to the diameter of the ZnO nanoparticles.
[0034] The ZnO nanowire of the present application is formed by ZnO nanoparticles with a particle size of 5-50 nm being connected to each other, and has a special string-bead structure. This structure not only maintains the characteristics of high aspect ratio and high specific surface area of the ZnO nanowire, but also exposes more active sites, which is beneficial to improve the catalytic performance, gas sensing performance and adsorption performance of the ZnO nanowire, so that the ZnO nanowire can be well applied in the fields of gas sensing, energy storage, catalysis or adsorption.
[0035] In a preferred embodiment, the particle size of the ZnO nanoparticles is 10-20 nm.
[0036] In a preferred embodiment, the diameter (i.e. width) of the ZnO nanowires is 30-150 nm, more preferably 50-100 nm.
[0037] In a preferred embodiment, the length of the ZnO nanowires is 1-10 μm, more preferably 2-6 μm.
[0038] The method for preparing the ZnO nanowires according to the present application comprises the following steps:
[0039] (1) mixing urea, water, a zinc source solution and a structure-directing agent to obtain a mixture;
[0040] (2) microwave heating the mixture;
[0041] (3) sintering the product obtained in step (2) at a temperature of 250-500°C;
[0042] The structure-directing agent is a water-soluble organic compound containing a pyrrolidone group.
[0043] In the method according to the present application, the zinc source is used to provide zinc ions; the main role of the urea is to react with zinc acetate to form an intermediate product, basic zinc carbonate; the structure-directing agent is a water-soluble organic compound containing a pyrrolidone group, which can strongly coordinate with zinc ions, thereby selectively adsorbing onto the surface of the precursor (basic zinc carbonate) and allowing the basic zinc carbonate particles to grow in a single direction to form a nanowire structure.
[0044] In the method according to the present application, if the sintering temperature is too low, the structure-directing agent will not be completely removed and the basic zinc carbonate will not be fully decomposed, thereby affecting the composition and structure of the product; if the sintering temperature is too high, the ZnO nanoparticles will fuse together, thereby forming a dense nanosheet structure, reducing the number and diameter of the pores and the number of surface active sites, and affecting the performance of the material. By sintering at a temperature of 250-500°C, the structure-directing agent can be more completely removed, preventing it from coating the surface of the nanomaterial and thereby affecting the performance of the nanomaterial; at the same time, the high temperature allows the basic zinc carbonate to decompose and oxidize, forming a string of beaded ZnO nanowires.
[0045] In the method according to the present application, a microwave-assisted hydrothermal method is used to prepare the string of beaded nanowires. Compared with the traditional hydrothermal method, microwave heating changes the heating source from a heat pipe to microwaves, so the heating is more uniform and there is no temperature gradient in the solution, thereby affecting the consistency of the nanomaterial; at the same time, the microwaves act directly at the molecular scale without a heat diffusion time, thereby greatly shortening the reaction time. Therefore, the microwave-assisted hydrothermal method is more suitable for large-scale production than the traditional hydrothermal method.
[0046] In a preferred embodiment, in step (1), the structure-directing agent is polyvinylpyrrolidone (PVP) and / or N-methylpyrrolidone (NMP), and the use of the above-mentioned substances makes the prepared ZnO nanowires have better performance (such as gas-sensing performance, catalytic performance, and adsorption performance, etc.).
[0047] Further preferably, the structure-directing agent is polyvinylpyrrolidone, and because polyvinylpyrrolidone contains polyvinyl groups, the specific surface area of the prepared nanowires is higher, and the gas-sensing performance is better.
[0048] In a specific embodiment, the weight-average molecular weight of the polyvinylpyrrolidone can be 5000-40000. It can be understood that the amount of substance of the polyvinylpyrrolidone is determined according to the weight-average molecular weight.
[0049] In a preferred embodiment, step (1) specifically comprises: mixing urea and water, then adding dropwise into a zinc source solution, and then mixing with a structure-directing agent to obtain a mixture.
[0050] In a specific embodiment, the zinc source solution is obtained by mixing a zinc source and water.
[0051] In a preferred embodiment, in step (1), the zinc source is selected from one or more than two of zinc acetate, zinc nitrate, and zinc sulfate.
[0052] If the concentration of the zinc source solution is too low, nanometal oxide particles will be obtained, and the string-bead structure cannot be formed. If the concentration is too high, the nanometal oxides will be too densely connected, and thus compact nanowires will be formed, and the string-bead structure cannot be formed. In the present application, in step (1), the concentration of the zinc source in the zinc source solution is 0.03-0.2 mol / L, and preferably 0.05-0.1 mol / L. For convenience of description, mol / L is referred to as M hereinafter.
[0053] In a preferred embodiment, in step (1), the molar ratio of the amounts of the zinc source, urea, and the structure-directing agent is 1:1.5-5:0.001-0.01, and more preferably 1:2-3:0.001-0.005.
[0054] The present application does not limit the specific amount of water added in step (1), as long as the urea can be dispersed sufficiently. In a specific embodiment, the weight-volume ratio of urea to water is 0.01-1 mol:1 L.
[0055] In a preferred embodiment, in step (2), the conditions for microwave heating in step (2) include: microwave power is 900-1500 kW, the reaction temperature is 90-150°C, and the reaction time is 10-50 min.
[0056] Further preferably, the microwave heating conditions include: microwave power of 1000-1200 kW, reaction temperature of 100-120℃, and reaction time of 10-30 min. Under the above conditions, the specific surface area of the ZnO nanowires prepared is larger, and the exposed active sites are more.
[0057] In specific embodiments, the microwave power of the microwave heating can be 1000 kW, 1050 kW, 1100 kW, 1150 kW or 1200 kW.
[0058] In specific embodiments, the reaction time of the microwave heating can be 10 min, 12 min, 15 min, 18 min, 20 min, 23 min, 25 min, 28 min or 30 min.
[0059] In specific embodiments, the reaction temperature of the microwave heating can be 100℃, 105℃, 110℃, 115℃, 118℃, 119℃ or 120℃.
[0060] The present application does not limit the time required for heating to the reaction temperature when microwave heating. In preferred embodiments, the heating time of the microwave heating is controlled to be 10-30 min, so that the heating rate is appropriate, and the performance of the ZnO nanowires prepared is better. Specifically, the heating time can be, for example, 10 min, 12 min, 15 min, 18 min, 20 min, 24 min, 25 min, 28 min or 30 min.
[0061] In preferred embodiments, in step (3), the sintering is performed at a temperature of 300-400℃. Specifically, the sintering temperature can be, for example, 300℃, 310℃, 320℃, 330℃, 350℃, 360℃, 370℃, 380℃ or 400℃.
[0062] In preferred embodiments, in step (3), the sintering time is 0.5-4 h. Specifically, it can be, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h or 4 h.
[0063] In specific embodiments, in step (3), the sintering is performed in an air atmosphere.
[0064] It can be understood that in the method described in the present application, the product obtained by microwave heating needs to be washed and dried before sintering.
[0065] Preferably, the obtained product is washed with ethanol and deionized water.
[0066] Preferably, the drying removes water by freeze-drying.
[0067] The method provided by the application prepares the bead-on-string ZnO nanowire through a simple microwave-assisted hydrothermal method, and the process is short in time and simple in operation, and is very suitable for large-scale production; the bead-on-string structure prepared by the method not only maintains the characteristics of high aspect ratio and high specific surface area of the ZnO nanowire, but also can expose more active sites, which is beneficial to improving the catalytic and gas-sensitive performance.
[0068] The application further provides a ZnO nanowire prepared by the method.
[0069] The application further provides application of the ZnO nanowire in the field of gas sensing, energy storage, catalysis or adsorption. The ZnO nanowire has high specific surface area, high aspect ratio and can expose more active sites, so that the gas-sensitive performance, adsorption performance and catalytic performance of the ZnO nanowire are excellent, and the ZnO nanowire can be well applied in the field of gas sensing, energy storage, catalysis or adsorption.
[0070] The application further provides a hydrogen sensor, which comprises a gas-sensitive material, and the gas-sensitive material comprises the ZnO nanowire. The ZnO nanowire has a special bead-on-string structure, high specific surface area and high aspect ratio, so that when the ZnO nanowire is applied to the gas-sensitive material of the hydrogen sensor, the response speed is fast, the sensitivity is high, and the selectivity is high.
[0071] The application will be described in detail through examples below, but the protection scope of the application is not limited thereto.
[0072] In the examples below, the experimental methods are all conventional methods in the field unless otherwise specified. The experimental materials used in the examples below are all commercially available unless otherwise specified.
[0073] In the examples and comparative examples below, polyvinylpyrrolidone (PVP) is purchased from Sigma-Aldrich, and the type number is PVP10, and the weight average molecular weight is 10000.
[0074] Example 1
[0075] (1) A zinc acetate solution with a concentration of 0.05M is prepared, urea and water are mixed to obtain a urea solution, 100mL of the urea solution is added dropwise into 100mL of the zinc acetate solution, after stirring uniformly, PVP is added and stirred uniformly to obtain a mixture, wherein the molar ratio of the amounts of zinc acetate, urea and PVP is 1:2:0.001;
[0076] (2) The mixture obtained in step (1) is added into a reaction kettle, and heated to 100°C by microwave, wherein the microwave power is 1000 kW, the temperature rising time is 10 min, and the reaction time is 30 min. Then, the obtained product is washed twice with ethanol and deionized water, and the water is removed by freeze drying to obtain a basic zinc carbonate powder;
[0077] (3) The basic zinc carbonate powder obtained in step (2) is placed into a tube furnace, and sintered in an air atmosphere (the sintering temperature is 300°C, and the sintering time is 1 h) to obtain the string-bead-shaped ZnO nanowires.
[0078] Example 2
[0079] (1) A zinc acetate solution with a concentration of 0.05 M is prepared, and urea and water are mixed to obtain a urea solution. 100 mL of the urea solution is added dropwise into 100 mL of the zinc acetate solution, and stirred uniformly. Then, PVP is added and stirred uniformly to obtain a mixture, wherein the molar ratio of the amounts of zinc acetate, urea and PVP is 1:3:0.005.
[0080] (2) The mixture obtained in step (1) is added into a reaction kettle, and heated to 100°C by microwave, wherein the microwave power is 1000 kW, the temperature rising time is 10 min, and the reaction time is 30 min. Then, the obtained product is washed twice with ethanol and deionized water, and the water is removed by freeze drying to obtain a basic zinc carbonate powder;
[0081] (3) The basic zinc carbonate powder obtained in step (2) is placed into a tube furnace, and sintered in an air atmosphere (the sintering temperature is 300°C, and the sintering time is 1 h) to obtain the string-bead-shaped ZnO nanowires.
[0082] Example 3
[0083] (1) A zinc acetate solution with a concentration of 0.06 M is prepared, and urea and water are mixed to obtain a urea solution. 100 mL of the urea solution is added dropwise into 100 mL of the zinc acetate solution, and stirred uniformly. Then, PVP is added and stirred uniformly to obtain a mixture, wherein the molar ratio of the amounts of zinc acetate, urea and PVP is 1:2.5:0.01.
[0084] (2) The mixture obtained in step (1) is added into a reaction kettle, and heated to 100°C by microwave, wherein the microwave power is 1000 kW, the temperature rising time is 10 min, and the reaction time is 30 min. Then, the obtained product is washed twice with ethanol and deionized water, and the water is removed by freeze drying to obtain a basic zinc carbonate powder;
[0085] (3) Put the basic zinc carbonate powder obtained in step (2) into a tube furnace, and sinter under air atmosphere (sintering temperature is 300°C, and sintering time is 1 h) to obtain the string-bead-shaped ZnO nanowires.
[0086] Example 4
[0087] (1) A zinc acetate solution with a concentration of 0.05 M is prepared, and urea and water are mixed to obtain a urea solution. 100 mL of the urea solution is added dropwise into 100 mL of the zinc acetate solution, and then PVP is added after uniform stirring to obtain a mixture, wherein the molar ratio of the amounts of zinc acetate, urea, and PVP is 1:2:0.003;
[0088] (2) The mixture obtained in step (1) is added into a reaction kettle, and then heated to 100°C by microwave, wherein the microwave power is 1000 kW, the temperature rising time is 10 min, and the reaction time is 30 min. Then, the obtained product is washed twice with ethanol and deionized water, and then dried by freeze drying to obtain a basic zinc carbonate powder;
[0089] (3) The basic zinc carbonate powder obtained in step (2) is put into a tube furnace, and sintered under air atmosphere (sintering temperature is 400°C, and sintering time is 1.5 h) to obtain the string-bead-shaped ZnO nanowires.
[0090] Example 5
[0091] (1) A zinc acetate solution with a concentration of 0.05 M is prepared, and urea and water are mixed to obtain a urea solution. 100 mL of the urea solution is added dropwise into 100 mL of the zinc acetate solution, and then PVP is added after uniform stirring to obtain a mixture, wherein the molar ratio of the amounts of zinc acetate, urea, and PVP is 1:2:0.001;
[0092] (2) The mixture obtained in step (1) is added into a reaction kettle, and then heated to 100°C by microwave, wherein the microwave power is 1000 kW, the temperature rising time is 10 min, and the reaction time is 30 min. Then, the obtained product is washed twice with ethanol and deionized water, and then dried by freeze drying to obtain a basic zinc carbonate powder;
[0093] (3) The basic zinc carbonate powder obtained in step (2) is put into a tube furnace, and sintered under air atmosphere (sintering temperature is 350°C, and sintering time is 3 h) to obtain the string-bead-shaped ZnO nanowires.
[0094] Example 6
[0095] (1) A zinc acetate solution with a concentration of 0.05M was prepared, and urea and water were mixed to obtain a urea solution. 100mL of the urea solution was added dropwise to 100mL of the zinc acetate solution, which was stirred uniformly. Then PVP was added and stirred uniformly to obtain a mixture, wherein the molar ratio of the amounts of zinc acetate, urea and PVP was 1:2:0.001.
[0096] (2) The mixture obtained in step (1) was added to a reaction kettle, and was heated to 120°C by microwave, wherein the microwave power was 1200kW, the temperature rising time was 10min, and the reaction time was 30min. Then the obtained product was washed twice with ethanol and deionized water, and the water was removed by freeze-drying to obtain a basic zinc carbonate powder.
[0097] (3) The basic zinc carbonate powder obtained in step (2) was placed in a tube furnace, and was sintered in an air atmosphere (sintering temperature was 300°C, and sintering time was 1h) to obtain a string-bead-shaped ZnO nanowire.
[0098] Example 7
[0099] (1) A zinc acetate solution with a concentration of 0.05M was prepared, and urea and water were mixed to obtain a urea solution. 100mL of the urea solution was added dropwise to 100mL of the zinc acetate solution, which was stirred uniformly. Then PVP was added and stirred uniformly to obtain a mixture, wherein the molar ratio of the amounts of zinc acetate, urea and PVP was 1:2:0.001.
[0100] (2) The mixture obtained in step (1) was added to a reaction kettle, and was heated to 110°C by microwave, wherein the microwave power was 1100kW, the temperature rising time was 10min, and the reaction time was 20min. Then the obtained product was washed twice with ethanol and deionized water, and the water was removed by freeze-drying to obtain a basic zinc carbonate powder.
[0101] (3) The basic zinc carbonate powder obtained in step (2) was placed in a tube furnace, and was sintered in an air atmosphere (sintering temperature was 300°C, and sintering time was 1h) to obtain a string-bead-shaped ZnO nanowire.
[0102] Example 8
[0103] The method described in Example 1 was implemented, except that the concentration of the zinc acetate solution was 0.1M.
[0104] Example 9
[0105] The method described in Example 1 was implemented, except that the zinc acetate was replaced by zinc nitrate.
[0106] Example 10
[0107] The method described in Example 1 was followed, except that PVP was replaced by NMP.
[0108] Comparative Example 1
[0109] The method described in Example 1 was followed, except that the sintering temperature was 200°C.
[0110] Comparative Example 2
[0111] The method described in Example 1 was followed, except that the structure-directing agent PVP was replaced by glucose.
[0112] Comparative Example 3
[0113] The method described in Example 1 was followed, except that the structure-directing agent PVP was replaced by polyvinyl alcohol.
[0114] Test Example 1
[0115] (1) The basic zinc carbonate obtained in step (2) of Example 1 and the finally obtained ZnO nanowires were observed using a scanning electron microscope. The results are as follows: Figure 1 and Figure 2 shown.
[0116] Figure 1 This is a scanning electron microscope image of basic zinc carbonate. Figure 1 It can be seen that nano basic zinc carbonate is composed of nanoparticles to form a beaded nanowire structure with a diameter of about 50 to 100 nm and a length of 2 to 6 μm.
[0117] Figure 2 The scanning electron microscope image of ZnO nanowires is Figure 2 It can be seen that ZnO nanoparticles with a particle size of 10 to 20 nm are interconnected to form a beaded ZnO nanowire structure. The ZnO nanowires have a diameter of approximately 50 to 100 nm and a length of 2 to 6 μm. Calculations also show that the average diameter of the ZnO nanowires is 50 nm, the average length is 5 μm, and the aspect ratio is 100.
[0118] Will Figure 1 and Figure 2 By comparison, it can be seen that, unlike basic zinc carbonate, the individual nanoparticles of ZnO are more tightly connected due to sintering.
[0119] (2) The basic zinc carbonate obtained in step (2) of Example 1 and the finally obtained ZnO nanowires were subjected to XRD detection. The results are as follows: Figure 3 and Figure 4 shown.
[0120] Figure 3 is the XRD pattern of basic zinc carbonate,Figure 3 It can be seen that the basic zinc carbonate has high crystallinity.
[0121] Figure 4 The XRD pattern of the ZnO nanowires is shown in Figure 2. Figure 4 It can be seen that the ZnO nanowires have high crystallinity.
[0122] (3) The ZnO nanowires prepared in Examples 2-10 were detected by scanning electron microscopy, and the results showed that the ZnO nanowires prepared in Examples 2-10 were formed by mutual connection of ZnO nanoparticles, the particle size of the ZnO nanoparticles was 5-50 nm, and the length-diameter ratio of the ZnO nanowires was 80-333.
[0123] (4) The product prepared in Comparative Example 1 was detected by XRD, and the results showed that the crystallinity of the obtained product (ZnO nanowires) was low, which might be caused by the too low heat treatment temperature.
[0124] (5) The products prepared in Comparative Examples 2-3 were observed by electron microscopy.
[0125] The results showed that the product prepared in Comparative Example 2 was ZnO nanoparticles, which might be caused by the fact that glucose could not be selectively adsorbed to the surface of the precursor (basic zinc carbonate), and the ZnO precursor grew isotropically.
[0126] The product prepared in Comparative Example 3 was ZnO nanoparticles, which might be caused by the fact that polyvinyl alcohol could not be selectively adsorbed to the surface of the precursor (basic zinc carbonate), and the ZnO precursor grew isotropically.
[0127] Test Example 2
[0128] The specific surface area of the ZnO products prepared in Examples and Comparative Examples was tested by BET, and the results are shown in Table 1.
[0129] Table 1
[0130]
[0131]
[0132] It can be seen from Table 1 that the ZnO nanowires prepared in Examples 1-10 of the present application have high specific surface area.
[0133] Test Example 3
[0134] The ZnO products prepared in Examples and Comparative Examples were used as gas sensitive materials to prepare hydrogen sensors, and the specific preparation method was as follows: the product was added to an organic solvent, ground into a slurry, and then coated on a ceramic tube to obtain a hydrogen sensor.
[0135] The hydrogen sensor is subjected to hydrogen response performance detection, and the detection method is as follows: the gas sensitive sensor is placed into a sealed cavity, a current is passed, the resistance R0 of the gas sensitive sensor under room temperature is recorded, then 50-20000ppm hydrogen with different concentrations is passed into the sealed cavity, the resistance of the gas sensitive sensor is reduced, after the resistance is stable, the resistance R1 of the sensor at this time is recorded, the response value of the gas sensitive sensor is calculated by the formula S=(R0-R1) / R0*100%, the response time is the time when the resistance is reduced by 90%, and the detection result is as shown in Table 2. Figure 5 and Table 2.
[0136] Table 2
[0137]
[0138]
[0139] As can be seen from Table 2, the ZnO nanowires obtained by the examples 1-10 of the present application can achieve sensitive and rapid response to hydrogen at room temperature when used as a gas sensitive material, which may be because the ZnO nanowires of the present application have a special string bead structure, which not only maintains the characteristics of high aspect ratio and high specific surface area of the ZnO nanowires, but also can expose more active sites.
[0140] The above describes the preferred embodiments of the present application, but the present application is not limited thereto. Within the technical concept of the present application, various simple modifications can be made to the technical solutions of the present application, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be considered as the disclosed content of the present application, and all fall within the protection scope of the present application.
Claims
1. A ZnO nanowire, characterized in that: The ZnO nanowires are formed by interconnecting ZnO nanoparticles, and the particle size of the ZnO nanoparticles is 5 to 50 nm; The aspect ratio of the ZnO nanowires is 80-350, and the specific surface area is 100-200m 2 / g.
2. The ZnO nanowire according to claim 1, characterized in that The diameter of the ZnO nanowire is 30-150 nm, and the length is 1-10 μm.
3. A method for preparing ZnO nanowires, characterized in that: The method comprises the following steps: (1) mixing urea, water, a zinc source solution, and a structure directing agent to obtain a mixture; (2) heating the mixture with a microwave; (3) sintering the product obtained in step (2) at 250-500° C.; Wherein, the structure directing agent is a water-soluble organic compound containing a pyrrolidone group.
4. The method according to claim 3, characterized in that In step (1), the structure directing agent is polyvinyl pyrrolidone and / or N-methyl pyrrolidone.
5. The method according to claim 3, characterized in that Step (1) specifically includes: Urea and water are mixed and then added dropwise to a zinc source solution, followed by mixing with a structure directing agent to obtain a mixture.
6. The method according to claim 3 or 5, characterized in that In step (1), the zinc source is selected from one or more of zinc acetate, zinc nitrate and zinc sulfate; Preferably, in step (1), the concentration of the zinc source in the zinc source solution is 0.03 to 0.2 mol / L.
7. The method according to claim 3 or 5, characterized in that In step (1), the molar ratio of the zinc source, urea and structure directing agent is 1:1.5-5:0.001-0.
01.
8. The method according to claim 3, characterized in that In step (2), the microwave heating conditions include: microwave power of 900-1500 kW, reaction temperature of 90-150° C., and reaction time of 10-50 min.
9. The method according to claim 3, characterized in that In step (3), the sintering time is 0.5 to 4 hours.
10. ZnO nanowires prepared by the method according to any one of claims 3 to 9.
11. Use of the ZnO nanowire according to any one of claims 1 to 2 and 10 in the fields of gas sensing, energy storage, catalysis or adsorption.
12. A hydrogen sensor, characterized in that: The hydrogen sensor comprises a gas-sensitive material, and the gas-sensitive material is the ZnO nanowire according to any one of claims 1-2 and 10.